ATA-ANANÍ QÁDIRLEW – MILLIY QÁDIRIYaT - Pazılov, A.K. (ILIM hám JÁMIYET, 2025)
The article provides information about problematic situations related to knowing the value of parents, personal observations, conversations, and attempts to use the obtained information in student audiences, and these materials encourage our youth to be faithful to our national values.